Sturm-Liouville Problem via Coulomb Type in Difference Equations - Bas, Erdal; Ozarslan, Ramazan (Univ Nis, Fac Sci Math, 2017)
We present Sturm-Liouville problem via Coulomb type in difference equations. The representation of solutions is found. We proved that these solutions satisfy the equation. Asymptotic formulas of eigenfunctions are set.
Keywords: Sturm-Liouville; difference equation; Coulomb potential; Schrodinger operator; eigenfunction; asymptotic formula